Hubungan Aktivitas Fisik dan Perilaku Makan dengan Status Gizi Pelajar Sekolah Dasar Islam Al-Falaah Ciputat - Siti Tiara Romadhoni; Erma Mexcorry Sumbayak; Anna Maria Dewajanthi (Jurnal Kedokteran Meditek, 2020)
Nutritional problems in children need attention because of their significant influence on children’s growth and development. Factors affecting nutritional status include physical activity, excessive energy intake and unbalanced energy expenditure which cause weight gain. In addition to physical activity, eating behavior contributes in the occurrence of nutritional problems. This study aimed to analyze the relationship between physical activity and eating behavior with the nutritional status among school children. This was a cross sectional study carried out among 96 school children (9-12 years old) at SDI Al-Falaah in 2018, selected by a simple random sampling. Validated questionnaires of Baecke Physical Activities and Child Eating Behavior were used for data collection. Bivariate analysis was used to analyze the effect of independent variables (physical activity and eating behavior) on the dependent variable (nutritional status). The study found a positive correlation between physical activity and nutritional status. School children with low physical activity had nutritional status which was above normal. Food avoidant inclined to have a lower nutritional status, whereas food approach had obese nutritional status. Bivariate analysis showed that there was a significant effect of physical activity and eating behavior on the nutritional status of Al-Falaah Islamic elementary school children.